Transformation of the French external cultural policy concept at the turn of the century - S. I. Kosenko (Vestnik MGIMO-Universiteta)
The variety of conceptual aspects of the Frances's external cultural policy is considered in the article through adjustments introduced to it by different governments which staggered each other since 1980s. The modern concept of the French cultural diplomacy was a result of a long historic evolution in the framework of the traditional action of its governors aimed at protection of cultural identity and national interests of their country. From its genesis in the Middle Ages in the form of voluntary acts by its Monarchs and further by Republican Presidents this very concept was never translated into a basic programmatic document. It happened only in 1983 within specific historical circumstances in a form of a doctrinal paper entitled "External cultural project of France" elaborated and approved by the government of socialists. Since that time, conventionally speaking, the doctrine of the external cultural action of France could be divided in three stock ideas: cultural "shining", cultural exception and cultural diversity which alternated each other.